Effect of seasonal sea ice breakout on the photosynthesis of benthic diatom mats at Casey, Antarctica - McMinn, A; Runcie, JW; Riddle, M (Journal of Phycology, 2004)
Photosynthesis of marine benthic diatom mats was examined before and after sea ice breakout at a coastal site in eastern Antarctica (Casey). Before ice breakout the maximum under-ice irradiance was between 2.5 and 8.2 mol photonsm-2s-1 and the benthic microalgal community was characterized by low Ek (12.1-32.3 mol photonsm-2s-1), low relETRmax (9.2-32.9), and high alpha (0.69-1.1). After breakout, 20 days later, the maximum irradiance had increased to between 293 and 840 mol photonsm-2s-1, Ek had increased by more than an order of magnitude (to 301-395 mol photonsm-2s-1), relETRmax had increased by more than five times (to 104-251), and alpha decreased by approximately 50% (to 0.42-0.68). During the same time interval the species composition of the mats changed, with a decline in the abundance of Trachyneis aspera (Karsten) Hustedt, Gyrosigma subsalsum Van Heurck, and Thalassiosira gracilis (Karsten) Hustedt and an increase in the abundance of Navicula glaciei Van Heurck. The benthic microalgal mats at Casey showed that species composition and photophysiology changed in response to the sudden natural increase in irradiance. This occurred through both succession shifts in the species composition of the mats and also an ability of individual cells to photoacclimate to the higher irradiances.